Peran Publik Relation KPID Sumatera Selatan Dalam Meningkatkan Literasi Media Masyarakat: Studi Fenomenologi - Hasyim, Kabillah; Saputra , Sepriadi (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The rapid development of information technology allows the public to easily access information through broadcasting and digital media platforms. However, the ability of society to comprehend and critically evaluate media content remains uneven, which contributes to the spread of misinformation and hoaxes. This study aims to explore the role of Public Relations at the Regional Indonesian Broadcasting Commission of South Sumatra (KPID South Sumatra) in enhancing media literacy among the community, as well as to identify the main challenges encountered in the implementation of media literacy programs. This research employs a qualitative method with a phenomenological approach, applying in-depth interviews, online observation, and public content analysis from internet-based sources. The findings indicate that KPID’s Public Relations performs an educational role through digital information dissemination, healthy broadcasting campaigns, and interactive communication services with the public. Nonetheless, limited human resources and the lack of community participation remain significant obstacles. The study highlights the need for stronger collaborative efforts across institutions to improve media literacy development evenly throughout South Sumatra